2009
DOI: 10.1007/s10681-009-0027-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of terminal water stress on leaf epicuticular wax load, residual transpiration and grain yield in barley

Abstract: The effect of drought on barley leaf epicuticular wax load (EWL), residual transpiration rates (RTR) and grain yield was examined by subjecting 12 barley genotypes to controlled irrigation and terminal water stress conditions. The mean leaf epicuticular wax load was found to be 9% greater in the plants subjected to terminal water stress than in those provided irrigation, while the mean residual transpiration rate of the irrigated plants was 20% higher than in those subjected to water stress. Under these stress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
65
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(70 citation statements)
references
References 44 publications
5
65
0
Order By: Relevance
“…The influence of loci previously identified for flag leaf glaucousness Previous reports on the effects of flag leaf glaucousness on cereal grain yield (Gonzalez and Ayerbe 2010;Johnson et al 1983;Richards et al 1986) and the large level of variation for this trait in the DH population (Bennett et al 2011) suggested that leaf glaucousness could be having a large effect on grain yield in the present study. QW.aww-3A accounted for a large percentage of variation for glaucousness, but in the present study, failed to exert influence on any other traits to a level where even a suggestive QTL could be detected.…”
Section: Discussionmentioning
confidence: 51%
“…The influence of loci previously identified for flag leaf glaucousness Previous reports on the effects of flag leaf glaucousness on cereal grain yield (Gonzalez and Ayerbe 2010;Johnson et al 1983;Richards et al 1986) and the large level of variation for this trait in the DH population (Bennett et al 2011) suggested that leaf glaucousness could be having a large effect on grain yield in the present study. QW.aww-3A accounted for a large percentage of variation for glaucousness, but in the present study, failed to exert influence on any other traits to a level where even a suggestive QTL could be detected.…”
Section: Discussionmentioning
confidence: 51%
“…The significance of residual transpiration (RT) with respect to yield is more controversial. González and Ayerbe (2010) found a negative correlation between RT and yield, which emphasizes the importance of water permeance of the cuticle under water stress. Other studies, however, have come to a different conclusion (Clarke et al, 1991).…”
Section: Discussionmentioning
confidence: 82%
“…Dark-adapted water loss has often been used as an indicator of residual transpiration (e.g. Kosma et al, 2009;González and Ayerbe, 2010), although incomplete closure of stomata in the dark may obviously have the potential to distort results. Applying this method to flag leaves of the selected wheat cultivars, a higher water loss rate of Cappelle Desprez was observed in comparison with the other cultivars (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…A mutant of wild barley, eibi1, with a very thin cutin layer, was hypersensitive to drought [83]. Breeding for improved WUE, tolerance and yield under water deficit conditions led to increased amounts of cuticle waxes, further confirming the link between drought tolerance and cuticle properties [84]. Thus, the increased biosynthesis of cuticle waxes seems to be an established plant response to dry conditions.…”
Section: Controlling Water Loss Through the Cuticlementioning
confidence: 88%